Can Facebook groups enhance continuing professional development of teachers? Lessons from Kenya. Issue 2 (14th March 2020) - Bett, Harry; Makewa, Lazarus
ABSTRACT: Continuing Professional Development (CPD) for teachers in Kenya suffers from challenges such as inadequate resources, poor planning, competing interests, among others. Besides being traditional in approach, most CPD sessions are far between to be meaningfully helpful. With increasing uptake of technology and number of social media users in Kenya, Facebook can be a potential platform to enhance teachers' professional development. This exploratory cross-sectional survey focussed on discussions teachers had in the month of February 2015 on one Facebook Group named 'Teachers of English'. A directed content analysis of the 647 posts following Shulman's category of teacher knowledge base revealed that interactions on the group centred on the teaching of English and Literature, as well as on other education-related matters. This study concludes that that Facebook Groups can be fertile avenues for teachers' ongoing professional development, especially in developing countries where such opportunities are scarce.